2017
DOI: 10.3390/molecules22091468
|View full text |Cite
|
Sign up to set email alerts
|

The Variation of Oncidium Rosy Sunset Flower Volatiles with Daily Rhythm, Flowering Period, and Flower Parts

Abstract: Oncidium is an important ornamental crop worldwide, and in recent years, the characteristics of the flower aroma have become a concern for breeders. This study used headspace solid-phase microextraction (HS-SPME) and gas chromatography/mass spectrometry (GC-MS) analysis of the volatile compounds to study the aroma characteristics of Onc. Rosy Sunset. A total of 45 compounds were identified, with the major compound being linalool. Onc. Rosy Sunset had the highest odor concentration from 10:00 to 12:00 and lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…Variation in volatile mixture across orchid species allows for reduced attractiveness to individuals and species, thereby increasing specificity to only selected few pollinator species, such as in bees for pollination of Catasetum species (Milet-Pinheiro and Gerlach 2017). Diurnal bees were known as diurnal pollinators for Phalaenopsis species (Chiu et al, 2017). A similar trend was also observed in the volatile emission of Phalaenopsis Nobby's Pacific Sunset, in which the volatile emission was most active during the morning (Yeh et al 2014) for emission of linalool, geraniol, and α-farnesene.…”
Section: Effect Of Different Observation Period On the Phalaenopsis Bellina Floral Scent Emissionsupporting
confidence: 63%
See 1 more Smart Citation
“…Variation in volatile mixture across orchid species allows for reduced attractiveness to individuals and species, thereby increasing specificity to only selected few pollinator species, such as in bees for pollination of Catasetum species (Milet-Pinheiro and Gerlach 2017). Diurnal bees were known as diurnal pollinators for Phalaenopsis species (Chiu et al, 2017). A similar trend was also observed in the volatile emission of Phalaenopsis Nobby's Pacific Sunset, in which the volatile emission was most active during the morning (Yeh et al 2014) for emission of linalool, geraniol, and α-farnesene.…”
Section: Effect Of Different Observation Period On the Phalaenopsis Bellina Floral Scent Emissionsupporting
confidence: 63%
“…A similar trend was also observed in the volatile emission of Phalaenopsis Nobby's Pacific Sunset, in which the volatile emission was most active during the morning (Yeh et al 2014) for emission of linalool, geraniol, and α-farnesene. Chiu et al (2017) also reported the highest odor emission in the morning from 10 am to 12 pm for Oncidium Rosy Sunset orchid. Interestingly, a similar study conducted by Chuang et al (2017) revealed otherwise, where emissions of volatiles monoterpene linalool and eucalyptol from P. bellina was detected in the afternoon.…”
Section: Effect Of Different Observation Period On the Phalaenopsis Bellina Floral Scent Emissionmentioning
confidence: 92%
“… 1 Tentatively identification of components based on GC-MS library (Wiley 7n). 2 literature retention indices obtain from [ 19 , 22 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] and reference were checked for all on DB-1. 3 Retention indices, using paraffin (C 5 –C 25 ) as references.…”
Section: Figurementioning
confidence: 99%
“…Cai et al [4] speculated that this phenomenon was caused by the hydrolysis and pyrolysis of the compounds during the extraction process. [19,22,[27][28][29][30][31][32][33][34][35][36] and reference were checked for all on DB-1. 3 Retention indices, using paraffin (C 5 -C 25 ) as references.…”
Section: Sdmentioning
confidence: 99%
“…Flower fragrance is determined by complex mixtures of volatile compounds, generally emitted from petals, sepals, and the gynostemium of orchids [2]. In plants, flower fragrance is mostly an adaptation for attracting insects for pollination or a defense against predation by herbivores [3].…”
Section: Introductionmentioning
confidence: 99%